Silicon particle, silicon-containing active material, negative electrode active material for secondary batteries, negative electrode and secondary battery
By employing silicon particles with specific surface area and crystallite diameter ratios, and a oriented (111) plane, the cycle characteristics of lithium ion secondary batteries are significantly improved, addressing the breakdown issues of previous silicon-based materials.
Patent Information
- Application Number
- JP2023111510
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-06
- Publication Date
- 2025-01-20
AI Technical Summary
Existing lithium ion secondary batteries using silicon as a negative electrode active material suffer from poor cycle characteristics due to the breakdown of silicon particles during repeated charging and discharging, despite improvements in cycle characteristics in previous technologies.
The use of silicon particles with a specific surface area ratio calculated by BET method to laser diffraction particle size distribution analyzer of 2 or more, combined with a crystallite diameter of 5 nm to 14 nm, and a degree of orientation of the (111) plane of 0.03 or more, along with a matrix phase containing silicon, oxygen, and carbon, enhances the cycle performance.
The proposed silicon particles and active materials exhibit improved cyclability and initial Coulombic efficiency, reducing the collapse of silicon particles and matrix phase during lithium ion insertion and extraction, leading to enhanced cycle life of the battery.
Smart Images

Figure 2025008900000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to silicon particles and a silicon-containing active material containing the silicon. The present invention also relates to a negative electrode active material for a secondary battery containing the silicon-containing active material, a negative electrode containing the negative electrode active material for a secondary battery, and a secondary battery containing the negative electrode. [Background technology]
[0002] Non-aqueous electrolyte secondary batteries are used in portable devices, hybrid and electric vehicles, home storage batteries, and the like, and are required to have a good balance of multiple properties such as electric capacity, safety, and operational stability. Furthermore, in recent years, with the miniaturization of various electronic devices and communication devices and the rapid spread of hybrid automobiles and the like, there has been a strong demand for the development of lithium ion secondary batteries that have higher capacity and further improved various battery characteristics, such as cycle characteristics and discharge rate characteristics, as a driving power source for these devices and the like.
[0003] Since silicon has a large theoretical electric capacity, its use as an anode active material has been considered for the purpose of increasing the capacity of lithium-ion secondary batteries. However, silicon has a large difference between the volume expansion when it absorbs lithium and the volume contraction when it releases it, and silicon particles are destroyed during repeated charging and discharging. As a result, secondary batteries using silicon as an anode active material have inferior cycle characteristics.
[0004] For the purpose of improving the cycle characteristics of a secondary battery using silicon as a negative electrode active material, for example, Patent Document 1 proposes a specific silicon or silicon alloy having an average particle size (D50), an average particle size (D90), a BET specific surface area by the BET method, and an oxygen content each falling within a specific range.
[0005] Patent Document 2 proposes a negative electrode active material that is made of silicon particles having specific surface conditions, sizes, shapes, etc., and a silicon-based inorganic compound that encapsulates the silicon particles, and has a specific chemical bond state of the silicon element. It has been shown that a secondary battery using such a negative electrode active material simultaneously exhibits high levels of charge / discharge capacity, initial coulombic efficiency, and cycle characteristics. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2021-180124 A [Patent Document 2] JP 2021-114483 A Summary of the Invention [Problem to be solved by the invention]
[0007] However, even in the active material for secondary batteries described in Patent Document 1, repeated charging and discharging caused particle destruction and the cycle characteristics were insufficient. Although the cycle characteristics were improved in Patent Document 2, further improvement in the cycle characteristics is being demanded due to the recent increasing demand for performance in secondary battery applications. Therefore, there is a demand for the development of an active material for lithium secondary batteries using silicon particles and having improved cycle characteristics.
[0008] The present inventors have investigated the shape of silicon particles, particularly the crystal plane of silicon particles, and have investigated active materials for secondary batteries having excellent cycle characteristics. As a result, they have found silicon particles that provide active materials for secondary batteries having excellent cycle characteristics for lithium secondary batteries. That is, an object of the present invention is to provide silicon particles for use as an active material for a secondary battery having excellent cycle characteristics. [Means for solving the problem]
[0009] The present invention has the following aspects. [1] Silicon particles having a ratio of a specific surface area calculated by a laser diffraction particle size distribution analyzer to a specific surface area determined by the BET method of 2 or more. [2] The specific surface area measured by the laser diffraction particle size distribution meter is 35 m 2 / g or more. Measurement method: Laser diffraction particle size distribution meter with red laser refractive index of 3.0, absorption rate of 0.2, blue laser refractive index of 2.6, absorption rate of 0.2, powder density of 2.3g / cm 3 The specific surface area is calculated from the particle size distribution obtained under the above conditions. [3] The specific surface area determined by the BET method is 80m 2 / g or more according to [1] or [2]. [4] Silicon particles according to any one of [1] to [3], having a crystallite diameter of 5 nm or more and 14 nm or less, calculated by the Scherrer method.
[0010] The present invention also has the following aspects. [5] A silicon-containing active material containing silicon particles having a ratio of a specific surface area determined by a BET method to a specific surface area calculated by a laser diffraction particle size distribution analyzer of 2 or more, and an orientation degree (F(111)) of the (111) plane of the silicon particles obtained by the Lotgering method in X-ray diffraction is 0.03 or more. [6] The silicon particles have a specific surface area of 35 m2 as determined by the following measurement method using a laser diffraction particle size distribution meter. 2 / g or more of the silicon-containing active material according to [5]. Measurement method: Laser diffraction particle size distribution meter with red laser refractive index of 3.0, absorption rate of 0.2, blue laser refractive index of 2.6, absorption rate of 0.2, powder density of 2.3g / cm 3 The specific surface area is calculated from the particle size distribution obtained under the above conditions. [7] The specific surface area determined by the BET method is 50m2 / g or less of the silicon-containing active material according to [5] or [6]. [8] The silicon particle-containing active material according to any one of [5] to [7], wherein the volume average particle size is 2 μm or more and 20 μm or less. [9] The silicon particle-containing active material according to any one of [5] to [8], wherein the crystallite size of silicon in the active material is 40 nm or less.
[10] The silicon-containing active material according to any one of [5] to [9], which contains a matrix phase containing silicon, oxygen, and carbon as main components.
[0011] Further, the present invention has the following aspects.
[11] A negative electrode active material for a secondary battery, comprising the silicon-containing active material according to any one of [5] to
[10] .
[12] A negative electrode comprising the negative electrode active material for a secondary battery according to
[11] .
[13] A secondary battery comprising the negative electrode according to
[12] . Effect of the Invention
[0012] According to the present invention, there is provided an active material for a secondary battery used in a lithium ion secondary battery, and a secondary battery containing the active material for a secondary battery as a negative electrode active material, which provides a secondary battery with excellent cycleability. [Brief description of the drawings]
[0013] [Figure 1] FIG. 1 is a schematic diagram of a laser diffraction particle size distribution meter according to the present invention. [Diagram 2] FIG. 1 is a schematic diagram of a laser diffraction particle size distribution meter according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The silicon particles of the present invention (hereinafter also referred to as "the present silicon particles") have a ratio of the specific surface area determined by the BET method to the specific surface area calculated by a laser diffraction particle size distribution analyzer of 2 or more. Here, the laser diffraction particle size distribution meter is a measuring instrument that measures the particle size distribution or particle size distribution of a sample by irradiating a laser beam onto the sample and measuring the angular dependence of the intensity of the light scattered by the sample. As shown in Fig. 1, when a laser beam is irradiated onto a sample, particle A, the sample, the laser beam is diffracted by the sample. According to the laser diffraction particle size distribution meter, if the sample is a large particle, strong light is scattered at a small angle relative to the laser beam. On the other hand, if the sample is a small particle, light is also scattered at a large angle. By measuring the scattered light intensity data at various angles, the angular dependence of the scattered light intensity, that is, the scattering pattern, is obtained. By comparing this with the theoretically calculated scattering patterns for spherical particles of various sizes, the particle size distribution or particle size distribution is calculated. The theoretical scattering pattern is usually calculated using a formula called the Mie theory, and the particle size is obtained as the diameter of a volume-equivalent sphere. For example, as shown diagrammatically in Figure 2, if the sample is not spherical but has an uneven surface, it is considered to be spherical with the same diffraction angle as the diffraction angle obtained from the diffraction angle of the laser light. Therefore, the diameter obtained from the diffraction angle is the equivalent sphere diameter with the same diffraction angle. The equivalent sphere surface area is calculated from this equivalent sphere diameter, and the obtained equivalent sphere surface area is multiplied by the total area of the sample measured based on the particle size distribution, and the obtained total area is divided by the mass to obtain the specific surface area. Therefore, the specific surface area obtained by a laser diffraction particle size distribution analyzer corresponds to the specific surface area of a sphere having the same diffraction angle.
[0015] On the other hand, the specific surface area determined by the BET method can be determined by nitrogen gas adsorption measurement, and is, for example, a specific surface area that can be measured using a specific surface area measuring device. In the case of particle A having an uneven surface as shown in FIG. 2, for example, the specific surface area determined by the BET method is the surface area including the area of the recesses, and is the value obtained by dividing the measured value of the surface area of particle A by the mass. Therefore, the BET specific surface area is considered to represent the actual specific surface area of the particle.
[0016] The silicon particles have a ratio of the specific surface area calculated by the laser diffraction particle size distribution meter (hereinafter also referred to as "specific surface area L") to the specific surface area determined by the BET method (hereinafter also referred to as "specific surface area B") of at least 2. Here, the ratio of the specific surface area B to the specific surface area L is the value obtained by dividing the specific surface area B by the specific surface area L, and the silicon particles satisfy the following formula (1). Specific surface area B / specific surface area L≧2 (1) As described above, the specific surface area L is the specific surface area when the particle is regarded as a sphere, since the particle size is the diameter of a volume-equivalent sphere and the surface area is calculated from the diameter of the volume-equivalent sphere. On the other hand, the specific surface area B is the specific surface area obtained by actual measurement. Since the silicon particles satisfy the above formula (1), this indicates that the actual specific surface area is significantly larger than the specific surface area calculated from the particle size. It is believed that the surface of the silicon particles has irregularities, etc., which results in a large surface area per unit mass, i.e., a large specific surface area.
[0017] It is believed that when lithium penetrates into and is released from silicon particles during charging and discharging of a lithium secondary battery, the silicon particles repeatedly expand and contract, causing them to collapse. In addition, when the active material described below is made of silicon particles and a matrix phase, the force generated during expansion and contraction is exerted on the surrounding matrix, making the active material more likely to collapse. As a result, it is believed that the cycle life of a lithium secondary battery using silicon particles is shortened, and the cyclability is reduced.
[0018] On the other hand, as described above, the silicon particles have an actual specific surface area that is considerably larger than the specific surface area calculated from the particle size, and the shape of the silicon particles is significantly different from a sphere with the particle size as the diameter, which indicates that the surface area is even larger than that of a sphere. By increasing the surface area in this way, it is believed that the force generated when lithium penetrates into and is released from the silicon particles during charging and discharging of the lithium secondary battery is dispersed, and the stress that collapses the silicon particles is reduced. As a result, it is believed that the silicon particles are less likely to collapse even when lithium penetrates into and is released from the silicon particles. Also, in the case of an active material consisting of silicon particles and a matrix phase, it is believed that the collapse of the matrix surrounding the silicon particles is suppressed, improving the cycle life and cyclability of the lithium secondary battery.
[0019] From the viewpoint of the cycle property of the resulting secondary battery, the ratio of the specific surface area B to the specific surface area L of the silicon particles of the present invention is preferably 2.5 or more, more preferably 2.8. The ratio of the specific surface area B to the specific surface area L of the silicon particles of the present invention is usually 1.3 or less.
[0020] From the viewpoint of the cycle property of the resulting secondary battery, the silicon particles have a specific surface area (hereinafter also referred to as "specific surface area LL") of 35 m2 as determined by the following measurement method for specific surface area using a laser diffraction particle size distribution meter. 2 / g or more is preferred. Measurement method: Laser diffraction particle size distribution meter with red laser refractive index of 3.0, absorption rate of 0.2, blue laser refractive index of 2.6, absorption rate of 0.2, powder density of 2.3g / cm 3 The specific surface area is calculated from the particle size distribution obtained under the above conditions. The refractive index and absorptivity of the red laser and blue laser are values obtained from literature, and the wavelength of the red laser is 630 nm to 780 nm, and the wavelength of the blue laser is 430 nm to 470 nm. The method for calculating the specific surface area LL is the same as the method for calculating the specific surface area L described above. The specific surface area LL of this silicon particle is 38m from the viewpoint of cycle characteristics.2 / g or more is more preferable, and 40m 2 From the viewpoint of initial Coulombic efficiency, the specific surface area LL of the silicon particles is preferably 130 m 2 / g or less is preferable, and 100m 2 / g or less is more preferable.
[0021] The specific surface area B of this silicon particle is 80m 2 / g or more is preferable from the viewpoint of electric capacity and initial coulombic efficiency. The specific surface area B of the silicon particles is set to be between 80 and 300 m from the viewpoint of capacitance and initial coulombic efficiency. 2 / g is more preferable, and 100 to 230m 2 / g is more preferred.
[0022] From the viewpoint of initial coulombic efficiency and capacity retention rate, in the X-ray diffraction method (hereinafter also referred to as XRD) of the present silicon particle, the crystallite diameter (hereinafter also referred to as "crystallite diameter") calculated by the Scherrer method from the diffraction peak belonging to the (111) plane of the silicon particle is preferably 5 nm or more and 14 nm or less. The crystallite diameter is more preferably 12 nm or less, and even more preferably 10 nm or less. The Scherrer method is a method for determining the crystallite diameter from powder XRD. The crystallite size, L, is expressed by the following formula (2) when the peak angle, θ, from the powder XRD and its half-width, β, are expressed as follows: L = Kλ / (βcosθ) (2) In formula (2), K is the Scherrer constant, which is usually set to 0.9, and λ is the wavelength of the X-rays used in the XRD.
[0023] The particle size of the silicon particles is preferably nano-order in volume average particle size. Small particle size improves cycle performance. The volume average particle size of the nano order means that the volume average particle size is in nanometer units, and the volume average particle size is usually 1 to 999 nm. If the silicon particles exceed 1000 nm, the dispersibility of the silicon particles when they are made into a silicon slurry during the preparation of the active material may deteriorate, the pressure during stirring may increase, and the productivity may decrease. From these viewpoints, the volume average particle size of the silicon particles is preferably 10 to 200 nm, more preferably 10 to 100 nm, and even more preferably 20 to 70 nm. The volume average particle size is the value of D50, which can be measured using the laser diffraction particle size analyzer. D50 can be measured by dynamic light scattering using a laser particle size analyzer. The volume average particle size of the present silicon particles is the particle size at which the cumulative volume distribution curve is drawn from the small diameter side in the particle size distribution, and the cumulative volume distribution curve is 50%.
[0024] The silicon particles may contain oxygen atoms. When the silicon particles contain oxygen atoms, the amount of oxygen atoms in the silicon particles is preferably 5 to 45 atm% relative to silicon atoms from the viewpoints of cycle performance, initial coulombic efficiency, and capacity retention rate when the silicon particles are used as a negative electrode active material of a secondary battery. When the silicon particles contain oxygen atoms, the amount of oxygen atoms in the silicon particles is preferably 5 to 30 atm%, more preferably 5 to 25 atm%, and even more preferably 5 to 15% from the viewpoints of initial coulombic efficiency and capacity retention. The amount of oxygen atoms can be measured by calcining the silicon particles at a temperature of 300 to 800° C. to volatilize the additives, and then performing composition analysis using SEM-EDS (JEOL, JSM-7900F). The silicon particles may contain carbon atoms and nitrogen atoms in addition to silicon atoms and the oxygen atoms. When nitrogen atoms are contained, the amount of nitrogen is preferably 5 mass % or less from the viewpoint of the capacity reduction due to the formation of silicon nitride.
[0025] The degree of orientation of the (111) plane, F(111), of the silicon particles obtained by the Lotgering method in XRD is preferably 0.2 or more. The Rod-Gehring method is a method for evaluating the degree of orientation using the Rod-Gehring factor, which is one of the indices that express the degree of orientation of a ceramic polycrystalline body. The Rod-Gehring factor is expressed by the following formula (3), and indicates 1 in the case of perfect orientation.
number
number
[0026] It is generally known that in the case of an active material having silicon particles and a matrix phase, stress on the matrix phase increases with expansion and contraction caused by lithium entering and leaving the silicon particles during charging and discharging of a lithium secondary battery. It is believed that this increase in stress makes the matrix phase more susceptible to destruction, and ultimately the active material more likely to collapse. As a result, it is believed that the cycle life of a lithium secondary battery using silicon particles is shortened, and the cyclability is reduced.
[0027] On the other hand, when the orientation degree of the (111) plane of the silicon particles is oriented to the (111) plane to a certain extent, the area of the (111) plane of the silicon particles is large, and it is considered that the stress in the vertical direction of the (111) plane when lithium penetrates into and is released from the silicon particles during charging and discharging of a lithium secondary battery is small. As a result, it is considered that when the silicon particles are used as an active material, the collapse of the active material can be further suppressed. Also, in the case of an active material having the silicon particles and a matrix phase, it may be possible to further relatively reduce the stress on the matrix phase, which is considered to suppress the destruction of the matrix phase and further suppress the collapse of the active material. From the above viewpoint, F(111) of the silicon particles is preferably 0.2 or more, more preferably 0.4 or more. Also, F is 1 or less as described above.
[0028] The active material containing the present silicon particles is not easily broken down even when lithium is inserted or released, and is therefore suitable for use as an active material for secondary batteries. From the viewpoint of cycle characteristics, an active material containing the present silicon particles, in which the degree of orientation of the (111) plane, F(111), obtained by the Lotgering method is 0.03 or more (hereinafter also referred to as the present active material), is suitable as an active material for secondary batteries. As long as the F(111) of the silicon particles is within the above range, the present active material may be the present silicon particles themselves, or may be an active material containing the present silicon particles and a matrix phase described below.
[0029] As described above, the ratio of the specific surface area B to the specific surface area L of the present silicon particles is 2 or more, and it is believed that this shape will not change, such as being destroyed, even during the active material production processes such as firing when making the active material and forming a matrix phase. From this viewpoint, it is considered that the ratio of the specific surface area B to the specific surface area L of the silicon particles in the active material maintains the shape. Therefore, it is considered that the ratio of the specific surface area B to the specific surface area L of the silicon particles in the active material is 2 or more.
[0030] Furthermore, if the F(111) of the silicon particles in the active material is 0.03 or more, the silicon particles in the active material are highly oriented in the (111) plane, the area of the (111) plane of the silicon particles is large, and it is considered that the stress in the vertical direction of the (111) plane when lithium penetrates into and is released from the silicon particles during charging and discharging of the lithium secondary battery is small. As a result, it is considered that the collapse of the active material can be further suppressed. Also, in the case of an active material having silicon particles and a matrix phase, it may be possible to further relatively reduce the stress on the matrix phase, which is considered to suppress the destruction of the matrix phase and further suppress the collapse of the active material. From the above viewpoint, it is more preferable that F(111) of the silicon particles in the present active material is 0.05 or more. Also, F is 1 or less as described above. The degree of orientation of silicon in this active material, F(111), is the degree of orientation of the (111) plane of silicon in the silicon-containing active material obtained from XRD by the 2θ-θ method and the Lotgering method, as described above, and is obtained from the above formulas (3) and (4).
[0031] In addition, it is considered that the preferred shapes of the specific surface area LL, the specific surface area B, etc. of the silicon particles of the present invention do not change during the active material production process. Therefore, these shapes of the silicon particles in the present active material are also maintained, and the resulting effects are the same as those described above, and similar effects can be expected in secondary batteries using the present active material.
[0032] From the above viewpoints, and from the viewpoint of the cycle characteristics of the obtained secondary battery, at least a part of the silicon particles in the present active material has a specific surface area LL of 35 m 2 / g or more.
[0033] From the viewpoint of the electric capacity and initial coulombic efficiency of the obtained secondary battery, at least a part of the silicon particles in the active material has a specific surface area B of 80 m 2 / g or more.
[0034] The specific surface area of this active material is 50m from the viewpoint of electrical capacity and initial coulombic efficiency.2 / g or less is preferable, and 1.0m 2 / g or more 50m 2 / g or less is more preferable. When the specific surface area is within the above range, the amount of solvent absorbed during electrode preparation can be appropriately maintained, and the amount of binder used to maintain binding properties can also be appropriately maintained. Note that the specific surface area is a value determined by the BET method as described above, and can be determined by nitrogen gas adsorption measurement, for example, by using a specific surface area measurement device.
[0035] If the average particle size of the active material is too small, the specific surface area will increase significantly, and when the active material is used as the negative electrode active material in a secondary battery, the reversible charge / discharge capacity per unit volume may decrease due to an increase in the amount of solid-phase interface electrolyte decomposition product (hereinafter, also referred to as "SEI") generated during charging and discharging. If the average particle size is too large, there is a risk of the active material peeling off from the current collector during the preparation of the electrode film. Therefore, the volume average particle diameter of the present active material is preferably 2 μm or more and 20 μm or less. The volume average particle diameter of the present active material is more preferably 2.5 μm or more, and particularly preferably 3.0 μm or more. The volume average particle diameter of the present active material is more preferably 15 μm or less, even more preferably 12 μm or less, and particularly preferably 10 μm or less. The volume average particle diameter is the value of D50.
[0036] In the XRD of the active material, the crystallite diameter of the silicon particles in the active material that is assigned to the (111) plane is preferably 40 nm or less from the viewpoint of the initial coulombic efficiency and the capacity retention rate, more preferably 35 nm or less, and further preferably 30 nm or less. The crystallite size is a value determined by the above-mentioned Scherrer method.
[0037] From the viewpoint of the stability of the active material for secondary batteries, it is preferable to use a silicon-containing active material (hereinafter also referred to as "the present composite active material") containing a matrix phase and the present silicon particles having an F(111) of 0.2 or more as the active material for secondary batteries. When the composite active material is used as an active material for a secondary battery, the matrix phase is a material capable of absorbing and releasing lithium ions. The material capable of absorbing and releasing lithium ions is a material that can absorb lithium ions into the matrix phase during charging of the battery and release lithium ions from the matrix phase during discharging. The absorption and release cycle is repeated in the lithium secondary battery. Examples of materials capable of absorbing and releasing lithium ions include graphite, silicon dioxide, titanium oxide, and compounds containing silicon, oxygen, and carbon, and the matrix phase is preferably composed of these materials. Among these materials, from the viewpoint of improving the initial efficiency and capacity maintenance rate, a matrix phase composed of a compound containing at least one of silicon and carbon, such as graphite, silicon dioxide, a compound containing silicon, oxygen, and carbon, is preferred, and a matrix phase composed of a compound containing silicon, oxygen, and carbon is more preferred. Compounds containing silicon, oxygen, and carbon include silicon oxycarbide.
[0038] Silicon oxycarbide is composed of compounds containing silicon, oxygen, and carbon, and among these, a structure containing a three-dimensional network structure of a silicon-oxygen-carbon skeleton and free carbon is preferred. Here, free carbon is carbon that is not contained in the three-dimensional skeleton of silicon-oxygen-carbon. Free carbon includes carbon that exists as a carbon phase, carbon that is bonded to carbon in the carbon phase, and carbon that is bonded to the silicon-oxygen-carbon skeleton and the carbon phase.
[0039] The silicon oxycarbide is preferably represented by the following formula (5): SiOxCy (5) In formula (5), x represents the molar ratio of oxygen to silicon, and y represents the molar ratio of carbon to silicon. When the present composite active material is used in a secondary battery, from the viewpoint of obtaining an advantageous balance between charge / discharge performance and capacity retention rate, 1≦x<2 is preferable, 1≦x≦1.9 is more preferable, and 1≦x≦1.8 is even more preferable. When the present composite active material is used in a secondary battery, from the viewpoint of the balance between the charge / discharge performance and the initial coulombic efficiency, 1≦y≦20 is preferable, and 1.2≦y≦15 is more preferable.
[0040] The above x and y can be obtained by measuring the mass content of each element and then converting it into a molar ratio (atomic number ratio). In this case, the oxygen and carbon contents can be quantified using an inorganic elemental analyzer, and the silicon content can be quantified using an inductively coupled plasma optical emission spectrometer (ICP-OES). It is preferable to measure x and y by the above-described method, but it is also possible to perform local analysis of the active material, obtain many measurement points of the content ratio data obtained thereby, and infer the content ratio of the entire active material. Examples of local analysis include energy dispersive X-ray spectroscopy (SEM-EDX) and electron probe microanalyzer (EPMA).
[0041] When the matrix phase is a silicon oxycarbide phase made of silicon oxycarbide and has a structure containing a three-dimensional network structure of a silicon-oxygen-carbon skeleton and free carbon, the silicon-oxygen-carbon skeleton in the silicon oxycarbide phase has high chemical stability, has a composite structure with free carbon, and exhibits small volume change with respect to the absorption and release of lithium. The silicon particles are tightly wrapped in a composite structure of a silicon-oxygen-carbon skeleton and free carbon, so that the volume change of the silicon particles with respect to the absorption and release of lithium is further suppressed. As a result, when the composite active material is used as a negative electrode active material, the silicon particles in the negative electrode play a role as a main component for expressing the charge and discharge performance, while the silicon oxycarbide phase further suppresses the destruction of the particles due to the volume change of the silicon particles during charge and discharge, and the cycle performance of the lithium secondary battery is further improved.
[0042] In addition, when the compound constituting the silicon oxycarbide phase has a three-dimensional network structure of a silicon-oxygen-carbon skeleton and a structure containing free carbon, the silicon-oxygen-carbon skeleton causes a change in the internal electron distribution of the silicon-oxygen-carbon skeleton due to the approach of lithium ions, and an electrostatic bond or a coordination bond is formed between the silicon-oxygen-carbon skeleton and the lithium ions. Lithium ions are stored in the silicon-oxygen-carbon skeleton by this electrostatic bond or coordination bond. On the other hand, since the coordination bond energy is relatively low, the desorption reaction of lithium ions is easily carried out. That is, it is considered that the silicon-oxygen-carbon skeleton can reversibly cause the insertion and desorption reactions of lithium ions during charge and discharge.
[0043] The silicon oxycarbide may contain nitrogen in addition to silicon, oxygen, and carbon. In the method for producing the present composite active material described later, nitrogen atoms contained in raw materials used, such as phenolic resins or polysiloxane compounds, other nitrogen compounds such as dispersants, and nitrogen gas used in the firing process, are used as atomic groups containing functional groups in the molecule, and the nitrogen atoms can be introduced into the silicon oxycarbide phase. When the silicon oxycarbide phase contains nitrogen, it tends to be excellent in charge-discharge performance and capacity retention rate when the present composite active material is used as a negative electrode active material. When the compound constituting the silicon oxycarbide phase is a compound containing silicon, oxygen, carbon, and nitrogen, the silicon oxycarbide phase preferably contains a compound represented by the following formula (6). SiOaCbNc (6) In formula (6), a represents the molar ratio of oxygen to silicon, b represents the molar ratio of carbon to silicon, and c represents the molar ratio of nitrogen to silicon. When the silicon oxycarbide phase contains the compound represented by the above formula (6), from the viewpoints of charge-discharge performance and capacity retention rate when the active material containing the present silicon particles is used in a secondary battery, 1 ≦ a ≦ 2, 1 ≦ b ≦ 20, 0 < c ≦ 0.5 are preferable, and 1 ≦ a ≦ 1.9, 1.2 ≦ b ≦ 15, 0 < c ≦ 0.4 are more preferable.
[0044] The above-mentioned a, b and c can be determined by measuring the mass contents of the elements and then converting them into molar ratios (ratio of atomic numbers), similarly to the above-mentioned x and y. As with x and y, it is preferable to measure a, b, and c by the above-described method, but it is also possible to perform local analysis of the active material, obtain many measurement points of the content ratio data obtained thereby, and infer the content ratio of the entire active material. Examples of local analysis include energy dispersive X-ray spectroscopy (SEM-EDX) and electron probe microanalyzer (EPMA).
[0045] In the case of an active material in which the matrix phase contains silicon oxycarbide, it is preferable that the silicon oxycarbide has a silicon-oxygen-carbon skeletal structure and free carbon composed only of carbon elements. When the silicon oxycarbide has free carbon, the active material has a Raman spectrum of 1590 cm 2 assigned to the G band of the graphite long-period carbon lattice structure. -1 and 1330 cm, which is assigned to the D band of the disordered and defective graphitic short-period carbon lattice structure. -1 A scattering peak around the scattering peak intensity is observed. The intensity ratio of the scattering peak intensity of the D band, I(D band), to the scattering peak intensity of the D band, I(G band), I(G band) / I(D band), is preferably 0.7 or more and 2 or less. The scattering peak intensity ratio, I(G band) / I(D band), is more preferably 0.7 or more and 1.8 or less. The fact that the scattering peak intensity ratio, I(G band) / I(D band), is in the above range means that the following can be said about the free carbon in the matrix.
[0046] Some carbon atoms of the free carbon are bonded to some silicon atoms in the silicon-oxygen-carbon skeleton. This free carbon is an important component that affects the charge-discharge characteristics. The free carbon is mainly formed in the silicon-oxygen-carbon skeleton composed of SiO2C2, SiO3C, and SiO4, and is bonded to some silicon atoms in the silicon-oxygen-carbon skeleton, so that electron transfer between the silicon atoms inside the silicon-oxygen-carbon skeleton and on the surface and the free carbon becomes easier. Therefore, when an active material in which the matrix phase contains silicon particles is used as the negative electrode active material in a secondary battery, the insertion and desorption reactions of lithium ions during charging and discharging proceed quickly, and the charge-discharge characteristics are improved. In addition, the insertion and desorption reactions of lithium ions may cause the active material to expand and contract, but the presence of free carbon in its vicinity is thought to have the effect of mitigating the expansion and contraction of the entire active material, greatly improving the capacity retention rate.
[0047] The free carbon is formed by pyrolysis of the silicon-containing compound and the carbon source resin in an inert gas atmosphere during the production of the silicon oxycarbide phase. Specifically, carbonizable sites in the molecular structures of the silicon-containing compound and the carbon source resin are converted into carbon components by high-temperature pyrolysis in an inactive atmosphere, and some of these carbons are bonded to a part of the silicon-oxygen-carbon skeleton. The carbonizable components are preferably hydrocarbons, more preferably alkyls, alkylenes, alkenes, alkynes, and aromatics, and even more preferably aromatics.
[0048] In addition, the presence of free carbon is expected to reduce the resistance of the active material, and when the active material is used as the negative electrode of a secondary battery, the reaction inside the active material occurs uniformly and smoothly, and it is believed that a secondary battery active material with an excellent balance between charge / discharge performance and capacity retention rate can be obtained. Although the introduction of free carbon is possible only from silicon-containing compounds, the use of a carbon source resin in combination is expected to increase the amount of free carbon present and its effect. The type of carbon source resin is not particularly limited, but a carbon compound containing a six-membered carbon ring is preferred.
[0049] The state of the free carbon can be identified by a thermogravimetric differential thermal analyzer (TG-DTA) in addition to Raman spectroscopy. Unlike the carbon atoms in a silicon-oxygen-carbon skeleton, free carbon is easily thermally decomposed in the atmosphere, and the amount of carbon present can be determined from the amount of thermal weight loss measured in the presence of air. In other words, the amount of carbon can be quantified using TG-DTA. In addition, from the thermal weight loss behavior, the changes in the thermal decomposition temperature behavior, such as the decomposition reaction start temperature, the decomposition reaction end temperature, the number of thermal decomposition reaction species, and the temperature of the maximum weight loss amount in each thermal decomposition reaction species, can be easily understood. The state of carbon can be determined using the temperature values of these behaviors. On the other hand, the carbon atoms in the silicon-oxygen-carbon skeleton, that is, the carbon atoms bonded to the silicon atoms constituting the SiO2C2, SiO3C, and SiO4, have a very strong chemical bond and are therefore highly thermally stable, and are not considered to be thermally decomposed in the air within the temperature range of the thermal analysis device measurement. In addition, the carbon in the silicon oxycarbide phase of the active material has properties similar to those of amorphous carbon, so it is thermally decomposed in the air in the temperature range of about 550°C to 900°C. As a result, a rapid weight loss occurs. The maximum temperature of the measurement conditions for TG-DTA is not particularly limited, but in order to completely terminate the thermal decomposition reaction of carbon, it is preferable to perform the TG-DTA measurement in the air under conditions of about 25°C to about 1000°C or higher.
[0050] The surface of the active material may be coated with a coating material, which is preferably a material that is expected to have electronic conductivity, lithium ion conductivity, and the effect of inhibiting decomposition of the electrolyte. The coating material includes electron conductive materials such as carbon, titanium, nickel, etc. Among these, from the viewpoint of improving the chemical stability and thermal stability of the active material, carbon is preferred, and low crystalline carbon is more preferred.
[0051] When the coating material is low-crystalline carbon, the average thickness of the coating layer is preferably 10 nm to 300 nm, and the content of low-crystalline carbon is preferably 1 to 30 mass % relative to 100 mass % of the total amount of the active material. When the coating material is carbon, the carbon coating is preferably formed on the surface of the active material by a vapor deposition method. The amount of the carbon coating is preferably 1% by mass to 10% by mass, based on the total mass of the active material and the carbon coating being 100% by mass, from the viewpoint of improving the chemical stability and thermal stability of the active material. The mass of the active material is the mass of the silicon particles having F(111) of 0.2 or more when the active material is composed only of the silicon particles having F(111) of 0.2 or more, and is the total amount of the silicon particles having F(111) of 0.2 or more and the matrix phase when the active material is composed of the silicon particles having F(111) of 0.2 or more. For example, when the matrix phase is made of silicon oxycarbide, it is the total amount of the silicon particles having F(111) of 0.2 or more and the silicon oxycarbide. When the silicon oxycarbide contains nitrogen, it is the total amount including the nitrogen. When the active material contains another third component described later, it is the total amount including the third component.
[0052] The present silicon particles are produced by pulverizing silicon chunks or the like into particles, and as described above, the ratio of the specific surface area B to the specific surface area L of the present silicon particles is 2 or more, and such silicon particles are silicon particles with a large surface area, for example, having irregularities on the surface. Therefore, when producing the present silicon particles, for example, a pulverization method that reduces the surface smoothness of the silicon particles can be used. As a method of crushing silicon particles that reduces the surface smoothness, for example, silicon chunks or the like are crushed with a relatively large force to produce silicon particles with a large particle size distribution. The silicon particles thus obtained are crushed with a relatively small force, and crushed with a force that causes peeling on the (111) plane of the silicon particles, thereby making it possible to obtain a ratio of the specific surface area B to the specific surface area L of the silicon particles. Examples of the pulverizer used for pulverizing the silicon chunks and the like to produce silicon particles include pulverizers such as a ball mill, a bead mill, a jet mill, etc. The pulverization may be wet pulverization using an organic solvent, and examples of the organic solvent include aromatic hydrocarbon solvents such as alcohols, ketones, toluene, xylene, naphthalene, and methylnaphthalene. At this time, by controlling conditions such as ball diameter, bead diameter, ejection pressure, pulverizer rotation speed, or pulverization time, it is possible to obtain particles with small diameters and uniform particle size distribution with a weak force that does not cause crushing. Then, pulverization can be performed under conditions that result in the movement of the balls or beads that provide a constant shear force. From the viewpoint of being able to control the shape anisotropy of the silicon particles, a pulverization method using a bead mill in which the bead diameter and pulverization time are controlled to pulverize the silicon particles is preferred.
[0053] For example, silicon chunks or the like can be pulverized using a pulverizer to a particle size of about 100 nm to 300 nm, and then, using a bead mill using beads with a diameter of, for example, 0.1 mm, the particles can be made into particles with a ratio of the specific surface area B to the specific surface area L of 2 or more. When the silicon particles are produced by a bead mill, the method of crushing the silicon particles by successively decreasing the average particle size of the beads from large to small in several steps can be used. For example, the method of crushing the silicon chunks to obtain large silicon particles having an average particle size of about 100 nm to 300 nm using beads having an average particle size of 0.5 mm or more for about 1 hour, and then crushing the silicon particles using beads having an average particle size of 0.1 mm or more and less than 0.5 mm for about 3 to 5 hours can be used.
[0054] Furthermore, in order to obtain particles having shape anisotropy with the (111) plane of the present silicon particles grown, for example, a method of crushing the present silicon particles so that the particle size of the present silicon particles is not made too small and the silicon particles exfoliate on the (111) plane can be mentioned. In this case, by controlling conditions such as the ball particle size, bead particle size, ejection pressure, grinder rotation speed, or grinding time so that the particle size does not become too small and the grinding energy is reduced, particles with a relatively small particle size can be obtained. After the particle size has been reduced to a certain degree, further crushing is performed with a weak force so that the silicon particles are peeled off from their (111) planes, thereby making it possible to obtain particles with shape anisotropy.
[0055] For example, silicon chunks or the like can be pulverized using a grinder to a particle size of about 100 nm to 500 nm, and then, using a bead mill using beads with a diameter of, for example, 0.05 mm, the silicon particles can be made into particles with shape anisotropy in which the (111) has grown. When the silicon particles are produced by a bead mill, the method of crushing the silicon particles by successively decreasing the average particle size of the beads from larger to smaller in several steps can be used. For example, the method of crushing the silicon chunks to obtain large silicon particles having an average particle size of 100 nm or more using beads having an average particle size of 0.2 mm or more for, for example, 1 hour or more, and then crushing the silicon particles for a long time, for example, 5 hours or more, using beads having an average particle size of 0.05 mm to 0.1 mm can be used.
[0056] If the purity of the silicon chunks used is less than 99% by mass, the metal may easily dissolve when the silicon particles are used as a negative electrode active material, making it difficult to handle the battery. Therefore, the purity of the silicon particles used is preferably 99% by mass or more, more preferably 99.9% by mass, and even more preferably 99.99% by mass.
[0057] The pulverization is usually carried out in an inert gas atmosphere, preferably a nitrogen atmosphere from the viewpoint of handling, and is preferably a wet pulverization in which silicon chunks or the like are pulverized in a non-aqueous solvent. Examples of non-aqueous solvents include ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and diisobutyl ketone; alcohols such as ethanol, methanol, normal propyl alcohol, and isopropyl alcohol; and aromatics such as benzene, toluene, and xylene. The concentration of the silicon chunks or the like in the non-aqueous solvent is about 5 to 50 mass %.
[0058] In the wet grinding, a dispersant may be added to promote grinding of silicon chunks, etc. The type of dispersant may be an aqueous or non-aqueous dispersant, and a non-aqueous dispersant is preferred. The type of non-aqueous dispersant may be a polymer type such as a polyether type, an alcohol type, a polyalkylene polyamine type, or a polycarboxylic acid partial alkyl ester type, a low molecular type such as a polyhydric alcohol ester type or an alkyl polyamine type, or an inorganic type such as a polyphosphate type. When the dispersant is added, the amount is preferably in the range of 5% by mass to 60% by mass, and more preferably 5% by mass to 30% by mass, based on the mass of the silicon chunks and the like.
[0059] Furthermore, in the wet grinding, at least one surfactant selected from the group consisting of cationic surfactants, anionic surfactants, and amphoteric surfactants may be added to improve the dispersibility of silicon lumps and the like and promote the grinding of silicon lumps and the like. Examples of cationic surfactants include aliphatic amine salts, aliphatic quaternary ammonium salts, aromatic quaternary ammonium salts, and heterocyclic quaternary ammonium salts. The amine value of the cationic surfactant is, for example, 1 to 100 mgKOH / g, preferably 5 to 80 mgKOH / g, more preferably 10 to 48 mgKOH / g, and particularly preferably 35 to 48 mgKOH / g. When the amine value is within the above range, re-aggregation of silicon particles nano-sized by pulverization can be suppressed, and the viscosity of the slurry can be suppressed, resulting in excellent cycle characteristics, charge / discharge capacity, and initial coulombic efficiency in the battery. Specifically, DISPERBYK9077 (manufactured by BYK Additives&Instruments, DISPERBYK is a registered trademark) can be used as the cationic surfactant.
[0060] Examples of the anionic surfactant include carboxylates, sulfonates, sulfates, and phosphates. The acid value of the anionic surfactant is, for example, 1 to 200 mgKOH / g, preferably 10 to 180 mgKOH / g, and more preferably 50 to 150 mgKOH / g. When the acid value is within the above range, the wettability of the silicon particles to the dispersion medium is improved, so that the viscosity of the slurry can be suppressed, and as a result, the cycle characteristics, charge / discharge capacity, and initial coulombic efficiency of the battery are excellent. Specifically, DISPERBYK111 (manufactured by BYK Additives&Instruments) can be used as the anionic surfactant.
[0061] The surfactant may be an amphoteric surfactant having the above amine value and acid value, or a cationic surfactant and an anionic surfactant having the above amine value and acid value may be used in combination. The amphoteric surfactant is a surfactant that exhibits the properties of an anionic surfactant in the alkaline range and the properties of a cationic surfactant in the acidic range, and examples of such surfactants include compounds containing carboxylates, amino acids, and betaines. Specifically, ANTI-TERRA (registered trademark)-U100 (manufactured by BYK Additives & Instruments) can be used as the amphoteric surfactant. When the surfactant is added, the amount added is preferably 5 to 60 mass %, more preferably 5 to 40 mass %, and further preferably 5 to 20 mass %, based on the mass of the silicon particles.
[0062] The silicon particles having an F(111) of 0.2 or more may be used as the active material as they are. When the present active material is the present composite active material, it can be produced, for example, by mixing the present silicon particles having an F(111) of 0.2 or more with a resin, drying the mixture, and then baking the mixture in an inert gas atmosphere. As described above, the matrix phase is composed of a material capable of absorbing and releasing lithium ions, so the resin to be mixed with the silicon particles having an F(111) of 0.2 or more may be any resin that becomes a material capable of absorbing and releasing lithium ions when baked. As described above, materials capable of absorbing and releasing lithium ions include graphite, silicon dioxide, titanium oxide, and compounds containing silicon, oxygen, and carbon, so examples of the resin to be mixed with the silicon particles having an F(111) of 0.2 or more include polysiloxane resins and carbon source resins.
[0063] When the present silicon particles having an F(111) of 0.2 or more are mixed with a resin, from the viewpoint of uniformly mixing the two, it is preferable to use the present silicon particles having an F(111) of 0.2 or more as a silicon particle slurry dispersed in a solvent. From the viewpoint of dispersibility, the silicon particle slurry is preferably a silicon particle slurry containing the present silicon particles having an F(111) of 0.2 or more, a dispersant, and a solvent. The dispersant contained in the silicon particle slurry is the same as above, and the solvent is water or the same non-aqueous solvent as the non-aqueous solvent. The preferred dispersant and non-aqueous solvent are also the same as above. The silicon particle slurry may also contain a surfactant. The surfactant may be at least one selected from the group consisting of the cationic surfactant, the anionic surfactant, and the amphoteric surfactant as above. The silicon particle slurry preferably contains silicon particles having an F(111) of 0.2 or more, a dispersant, and a non-aqueous solvent.
[0064] When the matrix phase of the composite active material contains the silicon oxycarbide, it is preferable to use a mixture of a polysiloxane compound and a carbon source resin as the resin.When the mixture of a polysiloxane compound and a carbon source resin is mixed with the silicon particles having an F(111) of 0.2 or more, it is preferable to use a silicon particle slurry having an F(111) of 0.2 or more. The slurry containing the silicon particles having an F(111) of 0.2 or more is mixed with a mixture of a polysiloxane compound and a carbon source resin, the solvent is removed to obtain a precursor, the precursor is calcined to obtain a calcined product, and the calcined product is pulverized as necessary to obtain the desired composite active material.
[0065] The polysiloxane compound may be a resin containing at least one of a polycarbosilane structure, a polysilazane structure, a polysilane structure, and a polysiloxane structure. The resin may be a resin containing only these structures, or a composite resin having at least one of these structures as a segment and chemically bonded to other polymer segments. The form of the composite may be graft copolymerization, block copolymerization, random copolymerization, alternating copolymerization, etc. For example, a composite resin having a graft structure in which a polysiloxane segment is chemically bonded to the side chain of a polymer segment, a composite resin having a block structure in which a polysiloxane segment is chemically bonded to the end of a polymer segment, etc. may be mentioned.
[0066] The polysiloxane segment is preferably a polysiloxane compound having a structural unit represented by the following general formula (S-1) and / or the following general formula (S-2): In particular, the polysiloxane compound more preferably has a carboxy group, an epoxy group, an amino group, or a polyether group on the side chain or terminal of the siloxane bond (Si-O-Si) main skeleton.
[0067] [ka]
[0068] [ka] In the general formulas (S-1) and (S-2), R 1 R represents an aromatic hydrocarbon group, an alkyl group, an epoxy group, a carboxy group, or the like, which may have a substituent. 2 and R 3respectively represent an alkyl group, a cycloalkyl group, an aryl group, an aralkyl group, an epoxy group, a carboxy group, or the like.
[0069] Examples of the alkyl group include a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, a pentyl group, an isopentyl group, a neopentyl group, a tert-pentyl group, a 1-methylbutyl group, a 2-methylbutyl group, a 1,2-dimethylpropyl group, a 1-ethylpropyl group, a hexyl group, an isohexyl group, a 1-methylpentyl group, a 2-methylpentyl group, a 3-methylpentyl group, a 1,1-dimethylbutyl group, a 1,2-dimethylbutyl group, a 2,2-dimethylbutyl group, a 1-ethylbutyl group, a 1,1,2-trimethylpropyl group, a 1,2,2-trimethylpropyl group, a 1-ethyl-2-methylpropyl group, a 1-ethyl-1-methylpropyl group, etc. Examples of the cycloalkyl group include a cyclopropyl group, a cyclobutyl group, a cyclopentyl group, a cyclohexyl group, etc.
[0070] Examples of the aryl group include a phenyl group, a naphthyl group, a 2-methylphenyl group, a 3-methylphenyl group, a 4-methylphenyl group, a 4-vinylphenyl group, and a 3-isopropylphenyl group.
[0071] Examples of the aralkyl group include a benzyl group, a diphenylmethyl group, and a naphthylmethyl group.
[0072] Examples of polymer segments other than the polysiloxane segment contained in the polysiloxane compound include vinyl polymer segments such as acrylic polymers, fluoroolefin polymers, vinyl ester polymers, aromatic vinyl polymers, and polyolefin polymers, as well as polymer segments such as polyurethane polymer segments, polyester polymer segments, and polyether polymer segments. Among these, vinyl polymer segments are preferred.
[0073] The polysiloxane compound may be a composite resin in which a polysiloxane segment and a polymer segment are bonded in a structure represented by the following structural formula (S-3), or may have a three-dimensional network polysiloxane structure.
[0074] [ka] In the formula, the carbon atom is a carbon atom that constitutes a polymer segment, and the two silicon atoms are silicon atoms that constitute a polysiloxane segment.
[0075] The polysiloxane segment of the polysiloxane compound may have a functional group capable of reacting by heating, such as a polymerizable double bond, in the polysiloxane segment. By subjecting the polysiloxane compound to heat treatment before thermal decomposition, a crosslinking reaction progresses and the compound is solidified, which makes it easy to carry out the thermal decomposition treatment.
[0076] Examples of the polymerizable double bond include a vinyl group and a (meth)acryloyl group. The number of polymerizable double bonds in the polysiloxane segment is preferably 2 or more, more preferably 3 to 200, and even more preferably 3 to 50. In addition, by using a composite resin having 2 or more polymerizable double bonds as the polysiloxane compound, the crosslinking reaction can be easily promoted.
[0077] The polysiloxane segment may have a silanol group and / or a hydrolyzable silyl group. Examples of the hydrolyzable group in the hydrolyzable silyl group include a halogen atom, an alkoxy group, a substituted alkoxy group, an acyloxy group, a phenoxy group, a mercapto group, an amino group, an amide group, an aminooxy group, an iminoxy group, and an alkenyloxy group. The hydrolyzable silyl group becomes a silanol group by hydrolysis of these groups. In parallel with the thermosetting reaction, a hydrolysis condensation reaction proceeds between the hydroxyl group in the silanol group and the hydrolyzable group in the hydrolyzable silyl group, thereby obtaining a solid polysiloxane compound.
[0078] The silanol group in the present invention is a silicon-containing group having a hydroxyl group directly bonded to a silicon atom. The hydrolyzable silyl group in the present invention is a silicon-containing group having a hydrolyzable group directly bonded to a silicon atom, and specifically includes, for example, a group represented by the following general formula (S-4).
[0079] [ka] In the formula, R 4 R represents a monovalent organic group such as an alkyl group, an aryl group, or an aralkyl group. 5 is a halogen atom, an alkoxy group, an acyloxy group, an allyloxy group, a mercapto group, an amino group, an amido group, an aminooxy group, an iminoxy group or an alkenyloxy group, and b is an integer of 0 to 2.
[0080] Examples of the alkyl group include a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, a pentyl group, an isopentyl group, a neopentyl group, a tert-pentyl group, a 1-methylbutyl group, a 2-methylbutyl group, a 1,2-dimethylpropyl group, a 1-ethylpropyl group, a hexyl group, an isohexyl group, a 1-methylpentyl group, a 2-methylpentyl group, a 3-methylpentyl group, a 1,1-dimethylbutyl group, a 1,2-dimethylbutyl group, a 2,2-dimethylbutyl group, a 1-ethylbutyl group, a 1,1,2-trimethylpropyl group, a 1,2,2-trimethylpropyl group, a 1-ethyl-2-methylpropyl group, and a 1-ethyl-1-methylpropyl group.
[0081] Examples of the aryl group include a phenyl group, a naphthyl group, a 2-methylphenyl group, a 3-methylphenyl group, a 4-methylphenyl group, a 4-vinylphenyl group, and a 3-isopropylphenyl group.
[0082] Examples of the aralkyl group include a benzyl group, a diphenylmethyl group, and a naphthylmethyl group.
[0083] Examples of the halogen atom include a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom.
[0084] Examples of the alkoxy group include a methoxy group, an ethoxy group, a propoxy group, an isopropoxy group, a butoxy group, a sec-butoxy group, and a tert-butoxy group.
[0085] Examples of the acyloxy group include a formyloxy group, an acetoxy group, a propanoyloxy group, a butanoyloxy group, a pivaloyloxy group, a pentanoyloxy group, a phenylacetoxy group, an acetoacetoxy group, a benzoyloxy group, and a naphthoyloxy group.
[0086] Examples of the allyloxy group include a phenyloxy group and a naphthyloxy group.
[0087] Examples of the alkenyloxy group include a vinyloxy group, an allyloxy group, a 1-propenyloxy group, an isopropenyloxy group, a 2-butenyloxy group, a 3-butenyloxy group, a 2-pentenyloxy group, a 3-methyl-3-butenyloxy group, and a 2-hexenyloxy group.
[0088] Examples of the polysiloxane segment having the structural unit represented by the general formula (S-1) and / or the general formula (S-2) include those having the following structures.
[0089] [ka]
[0090] [ka]
[0091] [ka]
[0092] The polymer segment may have various functional groups as necessary within the scope of not impairing the effects of the present invention. Examples of such functional groups include a carboxyl group, a blocked carboxyl group, a carboxylic anhydride group, a tertiary amino group, a hydroxyl group, a blocked hydroxyl group, a cyclocarbonate group, an epoxy group, a carbonyl group, a primary amide group, a secondary amide group, a carbamate group, and a functional group represented by the following structural formula (S-5).
[0093] [ka]
[0094] The polymer segment may also have a polymerizable double bond such as a vinyl group or a (meth)acryloyl group.
[0095] The polysiloxane compound is preferably produced, for example, by the following methods (i) to (iii).
[0096] (i) A method in which a polymer segment containing a silanol group and / or a hydrolyzable silyl group is prepared in advance as a raw material for the polymer segment, and this polymer segment is mixed with a silane compound having both a silanol group and / or a hydrolyzable silyl group and a polymerizable double bond, and a hydrolysis condensation reaction is carried out.
[0097] (ii) A method in which a polymer segment containing a silanol group and / or a hydrolyzable silyl group is prepared in advance as a raw material for the polymer segment. A polysiloxane is also prepared in advance by subjecting a silane compound having both a silanol group and / or a hydrolyzable silyl group and a polymerizable double bond to a hydrolysis and condensation reaction. The polymer segment and the polysiloxane are then mixed together to carry out a hydrolysis and condensation reaction.
[0098] (iii) A method in which the polymer segment, a silane compound having a silanol group and / or a hydrolyzable silyl group, and a polymerizable double bond, and a polysiloxane are mixed together, and a hydrolysis condensation reaction is carried out. A polysiloxane compound can be obtained by the above method. Examples of polysiloxane compounds include the Ceranate (registered trademark) series (organic / inorganic hybrid coating resin; manufactured by DIC Corporation) and the Compocelan SQ series (silsesquioxane hybrid; manufactured by Arakawa Chemical Industries, Ltd.).
[0099] The carbon source resin is preferably a synthetic resin or natural chemical raw material that has good miscibility with polysiloxane compounds, is carbonized by high-temperature baking in an inert atmosphere, and has an aromatic functional group.
[0100] Examples of synthetic resins include thermoplastic resins such as polyvinyl alcohol and polyacrylic acid, and thermosetting resins such as phenol resins and furan resins. Examples of natural chemical raw materials include heavy oils, particularly tar pitches, such as coal tar, light tar oil, medium tar oil, heavy tar oil, naphthalene oil, anthracene oil, coal tar pitch, pitch oil, mesophase pitch, oxygen-crosslinked petroleum pitch, and heavy oil. From the viewpoints of cheap availability and removal of impurities, the use of phenol resins is more preferable.
[0101] In particular, the carbon source resin is preferably a resin containing an aromatic hydrocarbon moiety, and the resin containing an aromatic hydrocarbon moiety is preferably a phenol resin, an epoxy resin, or a thermosetting resin, and the phenol resin is preferably a resol type. Examples of phenolic resins include SUMILITE resin series (resole type phenolic resins, manufactured by Sumitomo Bakelite Co., Ltd.).
[0102] The slurry containing the silicon particles having an F(111) of 0.2 or more is mixed with the mixture of the polysiloxane compound and the carbon source resin, and the solvent is removed to obtain a precursor. The mixture containing the polysiloxane compound and the carbon source resin is preferably in a state in which the polysiloxane compound and the carbon source resin are uniformly mixed. The mixing is performed using a device having the functions of dispersion and mixing. Examples of the device having the functions of dispersion and mixing include a stirrer, an ultrasonic mixer, and a premix disperser. In the work of desolvation and drying for the purpose of distilling off the organic solvent, a dryer, a reduced pressure dryer, a spray dryer, etc. can be used.
[0103] The precursor preferably contains 3% by mass to 50% by mass of the present silicon particles having an F(111) of 0.2 or more, 15% by mass to 85% by mass of a solid content of a polysiloxane compound, and 3% by mass to 70% by mass of a solid content of a carbon source resin, and more preferably contains 8% by mass to 40% by mass of the present silicon oxide particles, 20% by mass to 70% by mass of a solid content of a polysiloxane compound, and 3% by mass to 60% by mass of a solid content of a carbon source resin.
[0104] The precursor obtained above is calcined in an inert gas atmosphere to completely decompose the thermally decomposable organic components, thereby obtaining a calcined product. The calcination temperature is, for example, a maximum temperature in the range of 900°C to 1200°C, which allows the thermally decomposable organic components to be completely decomposed. The polysiloxane compound and the carbon source resin are converted by the energy of the high-temperature treatment into a silicon oxycarbide phase having a silicon-oxygen-carbon skeleton and free carbon.
[0105] Firing is carried out according to a firing program that specifies the heating rate, holding time at a constant temperature, etc. The maximum temperature is the highest temperature that can be set, and it strongly influences the structure and performance of the fired product. The maximum temperature can precisely control the microstructure of this active material, which retains the chemical bond state of silicon and carbon in the silicon oxycarbide phase, and can provide better charge / discharge characteristics.
[0106] The calcination method is not particularly limited, but a reaction device having a heating function in an inert gas atmosphere may be used, and treatment may be performed by a continuous method or a batch method. The calcination device may be appropriately selected from a fluidized bed reactor, a rotary furnace, a vertical moving bed reactor, a tunnel furnace, a batch furnace, a rotary kiln, etc. according to the purpose.
[0107] The obtained fired product is pulverized and classified as necessary to obtain the composite active material. The pulverization may be performed in one step to the desired particle size, or may be performed in several steps. For example, when preparing an active material of about 10 μm, the fired product of lumps or aggregates of 10 mm or more is coarsely pulverized to particles of about 1 mm using a jaw crusher, roll crusher, etc., and then pulverized to about 100 μm using a glow mill, ball mill, etc., and to about 10 μm using a bead mill, jet mill, etc. The particles produced by pulverization may contain coarse particles, and classification is performed to remove them, or to remove fine powder and adjust the particle size distribution. The classifier used is a wind classifier, a wet classifier, etc., depending on the purpose, but when removing coarse particles, a classification method that passes through a sieve is preferable because it can reliably achieve the purpose. In addition, if the precursor mixture is controlled to a shape near the target particle size by spray drying or the like before firing, and fired in that shape, it is possible to omit the pulverization process.
[0108] When the present composite active material has a silicate compound of at least one metal selected from the group consisting of Li, K, Na, Ca, Mg, and Al, the present active material having the silicate compound is obtained by mixing the slurry of the present silicon particles having an F(111) of 0.2 or more with a mixture of a polysiloxane compound and a carbon source resin, adding a salt of at least one metal selected from the group consisting of Li, K, Na, Ca, Mg, and Al to the suspension, and then performing the same operation as above. Examples of the salt of at least one metal selected from the group consisting of Li, K, Na, Ca, Mg, and Al include halides such as fluorides, chlorides, and bromides, hydroxides, and carbonates of these metals.
[0109] The salt of the metal may be a salt of two or more metals, one salt may have a plurality of metals, or it may be a mixture of salts having different metals. The amount of the metal salt added to the suspension is preferably 0.01 to 0.4 in terms of molar ratio relative to the number of moles of silicon oxide particles. When the metal salt is soluble in an organic solvent, the metal salt may be dissolved in an organic solvent and added to the suspension and mixed. When the metal salt is insoluble in an organic solvent, the metal salt particles may be dispersed in an organic solvent and then added to the suspension and mixed. From the viewpoint of improving the dispersion effect, the metal salt is preferably nanoparticles having an average particle size of 100 nm or less. As the organic solvent, alcohols, ketones, etc. can be suitably used, but aromatic hydrocarbon solvents such as toluene, xylene, naphthalene, and methylnaphthalene can also be used.
[0110] The present active material has excellent cycle properties, and a secondary battery using the present active material as a negative electrode active material for a secondary battery exhibits excellent characteristics. Specifically, a slurry containing the active material, an organic binder, and other components such as a conductive assistant, if necessary, can be applied to a copper foil collector in the form of a thin film to form a negative electrode. A carbon material such as graphite can also be added to the slurry to form a negative electrode. Examples of the carbon material include natural graphite, artificial graphite, and amorphous carbon such as hard carbon or soft carbon.
[0111] For example, the present active material and a binder, which is an organic binding material, are kneaded together with a solvent using a dispersing device such as a stirrer, a ball mill, a super sand mill, or a pressure kneader to prepare a negative electrode material slurry, which is then applied to a current collector to form a negative electrode layer. Alternatively, the negative electrode material can be obtained by forming a paste-like negative electrode material slurry into a sheet, pellet, or other shape and integrating it with a current collector.
[0112] Examples of the organic binder include styrene-butadiene rubber copolymers (hereinafter also referred to as "SBR"); ethylenically unsaturated carboxylic acid esters such as methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, (meth)acrylonitrile, and hydroxyethyl (meth)acrylate, and unsaturated carboxylic acid copolymers such as (meth)acrylic copolymers composed of ethylenically unsaturated carboxylic acids such as acrylic acid, methacrylic acid, itaconic acid, fumaric acid, and maleic acid; and polymer compounds such as polyvinylidene fluoride, polyethylene oxide, polyepichlorohydrin, polyphosphazene, polyacrylonitrile, polyimide, polyamideimide, and carboxymethylcellulose (hereinafter also referred to as "CMC").
[0113] Depending on their physical properties, these organic binders may be dispersed or dissolved in water, or dissolved in an organic solvent such as N-methyl-2-pyrrolidone (NMP), etc. The content of the organic binder in the negative electrode layer of the lithium ion secondary battery negative electrode is preferably 1 mass % to 30 mass %, more preferably 2 mass % to 20 mass %, and even more preferably 3 mass % to 15 mass %.
[0114] When the content of the organic binder is 1% by mass or more, the adhesion is better and the destruction of the negative electrode structure due to the expansion and contraction during charging and discharging is more suppressed, whereas when the content is 30% by mass or less, the increase in the electrode resistance is more suppressed. Within this range, the present active material has high chemical stability and can employ an aqueous binder, making it easy to handle in practical applications.
[0115] In addition, the negative electrode material slurry may be mixed with a conductive assistant as necessary. Examples of the conductive assistant include carbon black, graphite, acetylene black, and oxides and nitrides that exhibit conductivity. The amount of the conductive assistant used may be about 1% by mass to 15% by mass with respect to the negative electrode active material of the present invention.
[0116] The material and shape of the current collector may be, for example, a strip of copper, nickel, titanium, stainless steel, etc. in the form of foil, perforated foil, mesh, etc. Also, porous materials such as porous metal (foamed metal) and carbon paper can be used.
[0117] Examples of the method for applying the negative electrode material slurry to the current collector include metal mask printing, electrostatic coating, dip coating, spray coating, roll coating, doctor blade, gravure coating, screen printing, etc. After application, it is preferable to perform a rolling treatment using a flat plate press, a calendar roll, etc., as necessary.
[0118] The negative electrode material slurry may be formed into a sheet or pellet shape, and this may be integrated with the current collector by, for example, rolling, pressing, or a combination of these.
[0119] The negative electrode layer formed on the current collector or the negative electrode layer integrated with the current collector is preferably heat-treated according to the organic binder used. For example, when a water-based styrene-butadiene rubber copolymer (SBR) is used, the heat treatment may be performed at 100 to 130°C, and when an organic binder having a polyimide or polyamideimide as the main skeleton is used, the heat treatment is preferably performed at 150 to 450°C.
[0120] This heat treatment removes the solvent, hardens the binder, and increases the strength, improving the adhesion between the particles and between the particles and the current collector. It is preferable to carry out these heat treatments in an inert atmosphere such as helium, argon, or nitrogen, or in a vacuum atmosphere, in order to prevent oxidation of the current collector during the treatment.
[0121] In addition, it is preferable to subject the negative electrode to pressure treatment after the heat treatment. In the negative electrode using this active material, the electrode density is 1 g / cm 3 from 1.8 g / cm 3 and preferably 1.1 g / cm 3 to 1.7 g / cm 3More preferably, it is 1.2 g / cm 3 from 1.6 g / cm 3 It is more preferable that the electrode density is higher. The higher the electrode density, the more the adhesion and the volumetric capacity density of the electrode tend to improve. On the other hand, if the electrode density is too high, the voids in the electrode are reduced, which weakens the effect of suppressing the volume expansion of silicon, etc., and the capacity retention rate may decrease. Therefore, the optimal range of the electrode density is selected.
[0122] The secondary battery of the present invention contains the present active material in the negative electrode. As the secondary battery having a negative electrode containing the present active material, non-aqueous electrolyte secondary batteries and solid electrolyte secondary batteries are preferable, and the present active material exerts excellent performance particularly when used as the negative electrode of a non-aqueous electrolyte secondary battery.
[0123] When the secondary battery of the present invention is used as a wet electrolyte secondary battery, for example, the secondary battery can be constructed by disposing a positive electrode and a negative electrode containing the present silicon particle-containing negative electrode active material opposite each other via a separator and injecting an electrolyte solution.
[0124] The positive electrode can be obtained by forming a positive electrode layer on the surface of a current collector in the same manner as the negative electrode. In this case, the current collector can be a strip of a metal or alloy such as aluminum, titanium, or stainless steel in the form of a foil, a perforated foil, a mesh, or the like.
[0125] There are no particular limitations on the positive electrode material used in the positive electrode layer. When preparing a lithium ion secondary battery among non-aqueous electrolyte secondary batteries, for example, a metal compound, metal oxide, metal sulfide, or conductive polymer material capable of doping or intercalating lithium ions may be used. For example, lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMnO2), and composite oxides thereof (LiCoxNiyMnzO2, x+y+z=1), lithium manganese spinel (LiMn2O4), lithium vanadium compounds, V2O5, V6O 13, VO2, MnO2, TiO2, MoV2O8, TiS2, V2S5, VS2, MoS2, MoS3, Cr3O8, Cr2O5, olivine-type LiMPO4 (wherein M is Co, Ni, Mn, or Fe), conductive polymers such as polyacetylene, polyaniline, polypyrrole, polythiophene, polyacene, porous carbon, etc. can be used alone or in combination.
[0126] As the separator, for example, a nonwoven fabric, cloth, microporous film, or a combination thereof, mainly composed of polyolefin such as polyethylene or polypropylene can be used. Note that if the positive electrode and the negative electrode of the nonaqueous electrolyte secondary battery to be produced are not in direct contact with each other, there is no need to use a separator.
[0127] As the electrolyte, for example, a so-called organic electrolyte can be used in which a lithium salt such as LiClO4, LiPF6, LiAsF6, LiBF4, or LiSO3CF3 is dissolved in a non-aqueous solvent such as ethylene carbonate, propylene carbonate, butylene carbonate, vinylene carbonate, fluoroethylene carbonate, cyclopentanone, sulfolane, 3-methylsulfolane, 2,4-dimethylsulfolane, 3-methyl-1,3-oxazolidin-2-one, γ-butyrolactone, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, butyl methyl carbonate, ethyl propyl carbonate, butyl ethyl carbonate, dipropyl carbonate, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, methyl acetate, or ethyl acetate, or a mixture of two or more components.
[0128] The structure of the secondary battery of the present invention is not particularly limited, but usually, the positive electrode, the negative electrode, and a separator provided as necessary are wound into a flat spiral shape to form a wound electrode plate group, or these are stacked in a flat plate shape to form a stacked electrode plate group, and these electrode plate groups are sealed in an exterior body. Note that the half cells used in the examples of the present invention are configured so that the negative electrode is mainly made of the present active material, and a simple evaluation is performed using metallic lithium as the counter electrode, in order to more clearly compare the cycleability of the active material itself.
[0129] The secondary battery using the present active material is not particularly limited, but is used as a paper type battery, a button type battery, a coin type battery, a laminated type battery, a cylindrical type battery, a square type battery, etc. The above-mentioned negative electrode active material of the present invention can also be applied to electrochemical devices in general that use the insertion and desorption of lithium ions as a charge / discharge mechanism, such as hybrid capacitors and solid lithium secondary batteries.
[0130] As described above, when the present active material is used as the negative electrode active material of a secondary battery, it gives a secondary battery with excellent cycle properties. The present active material can be used as a negative electrode by the above-mentioned method to produce a secondary battery having the negative electrode.
[0131] While the present silicon particles, the present active material, the present active material-containing negative electrode active material, and the secondary battery including the present active material-containing negative electrode active material in the negative electrode have been described above, the present invention is not limited to the configurations of the above-described embodiments. In the configurations of the above-described embodiments of the present silicon particles, the present active material, and the present active material-containing negative electrode active material, as well as in a secondary battery containing the present active material-containing negative electrode active material in the negative electrode, any other configuration may be added, or any configuration that exhibits a similar function may be substituted. EXAMPLES
[0132] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these. In addition, the half-cell used in the examples of the present invention has a negative electrode mainly made of the present active material, and a simple evaluation is performed using metallic lithium as the counter electrode, in order to more clearly compare the cycle characteristics of the active material itself.
[0133] <Synthesis of silicon particles 1> 5000 g of commercially available silicon powder (manufactured by Kojundo Kagaku) with a silicon purity of 99.9% by mass and a volume average particle size of 3.2 μm, 2000 g of DISPERBYK9077 (manufactured by BYK Additives & Instruments, DISPERBYK is a registered trademark), and 20000 g of methyl ethyl ketone (hereinafter also referred to as "MEK") were mixed in a stirring tank and thoroughly stirred. The stirring tank was covered with a lid and nitrogen gas was supplied to create an inert gas atmosphere in the tank. This mixture was wet-pulverized for 1 hour using a bead mill (MSC Mill MSC220 manufactured by Nippon Coke Engineering Co., Ltd.) to obtain a silicon-containing slurry 1 in which silicon was uniformly dispersed in the dispersion medium. The diameter of the beads in the bead mill was 0.5 mm, and the peripheral speed of the bead mill was 12 m / s. 20,000 g of the silicon-containing slurry 1 was put into a stirring tank and thoroughly stirred. The stirring tank was covered with a lid and nitrogen gas was supplied to create an inert gas atmosphere inside the tank. The resulting solution was wet-milled for 4 hours using a bead mill (MSC Mill MSC220, manufactured by Nippon Coke & Engineering Co., Ltd.) to obtain a silicon-containing slurry 2 in which silicon was uniformly dispersed in the dispersion medium. At this time, the diameter of the beads used in the bead mill was 0.1 mm, and the density of the beads was 6.0 g / cm. 3 The bead filling rate was 70%, and the peripheral speed of the bead mill was 12 m / s.
[0134] <Synthesis of silicon particles 2> 5000 g of commercially available silicon powder (manufactured by Kojundo Kagaku) with a silicon purity of 99.9% by mass and a volume average particle size of 3.2 μm, 2000 g of DISPERBYK9077 (manufactured by BYK Additives & Instruments, DISPERBYK is a registered trademark), and 20000 g of MEK were mixed in a stirring tank and thoroughly stirred. The stirring tank was covered with a lid and nitrogen gas was supplied to create an inert gas atmosphere in the tank. This mixture was wet-pulverized for 1 hour using a bead mill (MSC Mill MSC220 manufactured by Nippon Coke & Engineering Co., Ltd.) to obtain a silicon-containing slurry 3 in which silicon was uniformly dispersed in the dispersion medium. The diameter of the beads in the bead mill was 0.5 mm, and the peripheral speed of the bead mill was 12 m / s. 20,000 g of the silicon-containing slurry 3 was put into a stirring tank and thoroughly stirred. The stirring tank was covered with a lid and nitrogen gas was supplied to create an inert gas atmosphere inside the tank. The resulting solution was wet-milled for 5 hours using a bead mill (MSC Mill MSC220, manufactured by Nippon Coke & Engineering Co., Ltd.) to obtain a silicon-containing slurry 4 in which silicon was uniformly dispersed in the dispersion medium. At this time, the diameter of the beads used in the bead mill was 0.1 mm, and the density of the beads was 6.0 g / cm. 3 The bead filling rate was 70%, and the peripheral speed of the bead mill was 12 m / s.
[0135] <Synthesis of silicon particles 3> 5000 g of commercially available silicon powder (manufactured by Kojundo Kagaku) with a silicon purity of 99.9% by mass and a volume average particle size of 3.2 μm, 2000 g of DISPERBYK9077 (manufactured by BYK Additives & Instruments, DISPERBYK is a registered trademark), and 20000 g of MEK were mixed in a stirring tank and thoroughly stirred. The stirring tank was covered with a lid and nitrogen gas was supplied to create an inert gas atmosphere in the tank. This mixture was wet-pulverized for 1 hour using a bead mill (MSC Mill MSC220 manufactured by Nippon Coke Engineering Co., Ltd.) to obtain a silicon-containing slurry 5 in which silicon was uniformly dispersed in the dispersion medium. The diameter of the beads in the bead mill was 0.5 mm, and the peripheral speed of the bead mill was 12 m / s. 20,000 g of the silicon-containing slurry 5 was put into a stirring tank and thoroughly stirred. The stirring tank was covered with a lid and nitrogen gas was supplied to create an inert gas atmosphere inside the tank. The resulting solution was wet-milled for 3 hours using a bead mill (MSC Mill MSC220 manufactured by Nippon Coke & Engineering Co., Ltd.) to obtain a silicon-containing slurry 6 in which silicon was uniformly dispersed in the dispersion medium. At this time, the diameter of the beads used in the bead mill was 0.1 mm, and the density of the beads was 6.0 g / cm. 3The filling rate of the beads was set to 70%, and the peripheral speed of the bead mill was set to 12 m / s.
[0136] <Synthesis of silicon particles 4> 5000 g of a commercially available silicon powder (manufactured by High Purity Chemicals) with a silicon purity of 99.9 mass% and a volume average particle diameter of 3.2 μm, 2000 g of DISPERBYK 9077 (manufactured by BYK Additives & Instruments, DISPERBYK is a registered trademark), and 20000 g of MEK were mixed in a stirring tank and stirred well. The stirring tank was covered and nitrogen gas was supplied to make the inside of the tank an inert gas atmosphere. This mixed solution was wet pulverized for 1 hour using a bead mill (MSC mill MSC220 manufactured by Nippon Coke & Engineering Co., Ltd.) to obtain a silicon-containing slurry 7 in which silicon was uniformly dispersed in the dispersion medium. The diameter of the beads in the bead mill was 0.2 mm, and the peripheral speed of the bead mill was 12 m / s. 20000 g of the above-mentioned silicon-containing slurry 7 was charged into a stirring tank and stirred well. The stirring tank was covered and nitrogen gas was supplied to make the inside of the tank an inert gas atmosphere. The obtained solution was wet pulverized for 2.5 hours using a bead mill (MSC mill MSC220 manufactured by Nippon Coke & Engineering Co., Ltd.) to obtain a silicon-containing slurry 8 in which silicon was uniformly dispersed in the dispersion medium. At this time, the diameter of the beads used in the bead mill was 0.1 mm, the density of the beads was 6.0 g / cm 3 The filling rate of the beads was set to 70%, and the peripheral speed of the bead mill was set to 12 m / s.
[0137] <Silicon particles 5> Commercially available spherical silicon particles were used as they were. The particle size of the silicon particles was 50 nm. <Silicon particles 6> Commercially available spherical silicon particles were used as they were. The particle size of the silicon particles was 100 nm.
[0138] <BET specific surface area> The silicon-containing slurry 2 was dried, and then heated in nitrogen at 500 °C to remove the dispersant adhering to the surface of the silicon particles. The specific surface area of this powder was calculated by the BET formula using the gas adsorption - constant volume method.
[0139] In the measurement of the BET specific surface area, the silicon-containing slurry 2 was changed to silicon-containing slurries 4, 6 and 8, and the BET specific surface areas of silicon particles 2 to 4 were determined. The results are shown in Table 1. In addition, for silicon particles 5 and 6, the specific surface areas of the powders of silicon particles 5 and 6 were calculated by the BET formula using the gas adsorption method-constant volume method.
[0140] <Laser diffraction particle size distribution measurement> The particle size distribution was measured by a laser diffraction particle size distribution meter using the same solvent as that used for the silicon-containing slurries 2, 4, 6, and 8. In this laser diffraction particle size distribution measurement, the value changes depending on the parameters used, so this time the measurement was performed with the following parameters. Red laser refractive index: 3.0, absorption rate: 0.2 Blue laser refractive index: 2.6, absorption rate: 0.2 Powder density: 2.3g / cm 3 The wavelength of the red laser was 630nm to 780nm, and the wavelength of the blue laser was 430nm to 470nm. D50 was measured five or more times under the above conditions, and the CV value (standard deviation / average value) of D50 was 5% or less for five consecutive measurements, confirming the stability of the measurement. Then, the specific surface area was calculated from the particle size distribution obtained by the above parameters.
[0141] <Specific surface area measured by laser diffraction particle size distribution analyzer> The specific surface area of the silicon particles was determined from the particle size distribution obtained by the laser diffraction particle size distribution measurement.
[0142] <Crystallite diameter> The silicon-containing slurries 2, 4, 6 and 8 were dried in the air, pulverized in a mortar, and subjected to 2θ-θ measurement by XRD, and the crystallite sizes of silicon particles 1 to 4 were measured using Rigaku's SmartLab. For silicon particles 5 and 6, the powder was used as it was. Using the full width at half maximum (FWHM) of the peak, the crystallite size of the (111) plane was calculated from the following formula (2) by the Scherrer method. The measurement angle was in the range of 10° to 70°. =Kλ / (βcosθ) (2) In the above formula (2), K is the Scherrer constant and is set to 0.9. λ is the wavelength of the X-ray used in the measurement, CuKα=1.5418 Å. β is the peak half-width in radians, θ is the Bragg angle corresponding to the (111) plane, and L is the crystallite diameter.
[0143] The XRD measurements were performed using a Cu tube at a tube voltage of 40 kV, a tube current of 40 mA, and a goniometer operation speed of 2° / min, using a Rigaku Corporation SmartLab as the measurement device.
[0144] Synthesis Example 1 of Active Material Precursor Resin <Preparation of polysiloxane compound> (Synthesis of methyltrimethoxysilane condensate (a1)) A reaction vessel equipped with a stirrer, a thermometer, a dropping funnel, a cooling tube, and a nitrogen gas inlet was charged with 1,421 parts by mass of methyltrimethoxysilane (hereinafter, referred to as "MTMS") and heated to 60° C. Next, a mixture of 0.17 parts by mass of isopropyl acid phosphate ("Phoslex A-3" manufactured by SC Organic Chemical Co., Ltd.) and 207 parts by mass of deionized water was dropped into the reaction vessel over a period of 5 minutes, and the mixture was stirred at a temperature of 80° C. for 4 hours to carry out a hydrolysis and condensation reaction of MTMS. The condensate obtained by the hydrolysis and condensation reaction was distilled at a temperature of 40 to 60°C and under a reduced pressure of 40 to 1.3 kPa. The phrase "under a reduced pressure of 40 to 1.3 kPa" means that the reduced pressure condition at the start of methanol distillation is 40 kPa, and the pressure is finally reduced to 1.3 kPa. The same applies to the following description. By removing the methanol and water produced during the reaction, 1,000 parts by mass of a liquid containing a condensate of MTMS having a number average molecular weight of 1,000 to 5,000 (hereinafter also referred to as "a1"). The content of the active ingredient in the obtained liquid was 70% by mass. The effective component is calculated by dividing the theoretical yield (parts by mass) when all methoxy groups of a silane monomer such as MTMS undergo a condensation reaction by the actual yield (parts by mass) after the condensation reaction, i.e., [theoretical yield (parts by mass) when all methoxy groups of a silane monomer undergo a condensation reaction / actual yield (parts by mass) after the condensation reaction].
[0145] <Production of Curable Resin Composition> A reaction vessel equipped with a stirrer, a thermometer, a dropping funnel, a cooling tube, and a nitrogen gas inlet was charged with 150 parts by mass of butanol (hereinafter also referred to as "BuOH"), 105 parts by mass of phenyltrimethoxysilane (hereinafter also referred to as "PTMS"), and 277 parts by mass of dimethyldimethoxysilane (hereinafter also referred to as "DMDMS"), and the temperature was raised to 80°C. Next, at the same temperature, a mixture containing 21 parts by mass of methyl methacrylate (hereinafter also referred to as "MMA"), 4 parts by mass of butyl methacrylate (hereinafter also referred to as "BMA"), 3 parts by mass of butyric acid (hereinafter also referred to as "BA"), 2 parts by mass of methacryloyloxypropyltrimethoxysilane (hereinafter also referred to as "MPTS"), 3 parts by mass of BuOH, and 0.6 parts by mass of butylperoxy-2-ethylhexanoate (hereinafter also referred to as "TBPEH") was dropped into the reaction vessel over 6 hours. After the dropwise addition was completed, the mixture was further reacted at the same temperature for 20 hours to obtain an organic solvent solution of a vinyl polymer (a2) having a number average molecular weight of 10,000 and having a hydrolyzable silyl group.
[0146] Next, a mixture of 0.04 parts by mass of isopropyl acid phosphate ("Phoslex A-3" manufactured by SC Organic Chemical Co., Ltd.) and 112 parts by mass of deionized water was added dropwise over a period of 5 minutes, and the mixture was stirred at the same temperature for a further 10 hours to cause a hydrolysis condensation reaction, thereby obtaining a liquid containing a composite resin in which the hydrolyzable silyl group of the vinyl polymer (a2) and the hydrolyzable silyl group and silanol group of the polysiloxane derived from the PTMS and DMDMS were bonded together. Next, 472 parts by mass of the MTMS condensate (a1) obtained by the above synthesis and 80 parts by mass of deionized water were added to this liquid, and the mixture was stirred at the same temperature for 10 hours to cause a hydrolysis condensation reaction, and the produced methanol and water were removed by distillation under the same conditions as in Synthesis Example 1. Next, 250 parts by mass of BuOH was added to obtain 1,000 parts by mass of a curable resin composition with a non-volatile content of 60.1% by mass.
[0147] <Preparation of negative electrode active material powder> Examples 1 to 3 The silicon particles 1 to 3 that had completed the above property evaluation were mixed in an agitation tank in an amount of 5,000 g, DISPERBYK9077 (manufactured by BYK Additives & Instruments, DISPERBYK is a registered trademark) in an amount of 2,000 g, and methyl ethyl ketone (hereinafter also referred to as "MEK") in an amount of 20,000 g, and the mixture was thoroughly stirred. The agitation tank was covered with a lid and nitrogen gas was supplied to create an inert gas atmosphere in the tank. The silicon-containing slurry, the above-mentioned curable resin composition, and a phenolic resin (manufactured by Sumitomo Bakelite, SUMILITE RESIN PR-53570) were mixed so that the composition after firing was calculated to be SiOC / C / Si=10 / 40 / 50, and charged into a three-necked separable flask. One neck was covered, and a nitrogen inlet tube and a solvent trap were connected to the remaining two necks. Nitrogen was introduced into the flask, and the mixture was stirred with a magnetic stirrer while the flask was heated to 120°C in an oil bath, dried, and the solvent was distilled off until the viscosity reached such that the stirrer no longer moved. After that, it was cooled to room temperature to obtain a dried resin material, which is a firing precursor. Then, the dried resin material, which is a firing precursor, was fired in a nitrogen atmosphere at a temperature of 1050°C for 6 hours to obtain a black solid material. The obtained black solid material was pulverized with a planetary ball mill to obtain negative electrode active materials 1 to 3.
[0148] Comparative Examples 1 to 3 Negative electrode active materials 4 to 6 were obtained in the same manner as in Examples 1 to 3 using silicon particles 4 to 6.
[0149] [Charge / discharge measurement evaluation] A mixed slurry containing 80% by mass of the negative electrode active materials 1 to 6, 10% by mass of acetylene black as a conductive additive, and 10% by mass of a mixture of CMC and SBR as a binder was prepared and formed on a copper foil. It was then dried under reduced pressure at 110°C and a Li metal foil was used as the counter electrode to prepare a half cell. A charge / discharge test was performed on this half cell using a two-phase battery charge / discharge measuring device (manufactured by Hokuto Co., Ltd.) with a cutoff voltage range of 0.005 to 1.5 V and a current value equivalent to 0.1 C. The results of this test were used to calculate the capacity loss rate after 20 cycles using the following formula: Capacity loss rate after 20 cycles = (discharge capacity at 21st cycle) / (discharge capacity at 2nd cycle) x 100
[0150] The results of the capacity reduction rates after 20 cycles of the negative electrode active materials 1 to 9 obtained by the above method are summarized in Table 1.
[0151] [Table 1]
[0152] <Synthesis of silicon particles 7 to 11> 5000 g of commercially available silicon powder (manufactured by Kojundo Kagaku) with a silicon purity of 99.9% by mass and a volume average particle size of 3.2 μm, 2000 g of DISPERBYK9077 (manufactured by BYK Additives & Instruments, DISPERBYK is a registered trademark), and 20000 g of MEK were mixed in a stirring tank and thoroughly stirred. The stirring tank was covered with a lid and nitrogen gas was supplied to create an inert gas atmosphere in the tank. This mixture was wet-milled for 1 hour using a bead mill (MSC Mill MSC220 manufactured by Nippon Coke Engineering Co., Ltd.) with a bead diameter of 0.5 mm and a peripheral speed of 12 m / s to obtain silicon-containing slurry 9 in which silicon is uniformly dispersed in the dispersion medium, and wet-milled for 2 hours with the same bead diameter and peripheral speed to obtain silicon-containing slurry 10 in which silicon is uniformly dispersed in the dispersion medium. The silicon-containing slurry 9 was put into a stirring tank in an amount of 20,000 g and thoroughly stirred. The stirring tank was covered with a lid and nitrogen gas was supplied to create an inert gas atmosphere inside the tank. The obtained solution was wet-pulverized using a bead mill (MSC Mill MSC220 manufactured by Nippon Coke & Engineering Co., Ltd.) for 3.5 hours for silicon particles 7, 2.75 hours for silicon particles 8, 3.25 hours for silicon particles 9, and 2 hours for silicon particles 11, to obtain silicon-containing slurries containing silicon particles 7, 8, 9, or 11 in which silicon is uniformly dispersed in a dispersion medium. In each case, the diameter of the beads used in the bead mill was 0.1 mm, and the density of the beads was 6.0 g / cm. 3 The bead filling rate was 70%, and the peripheral speed of the bead mill was 12 m / s. In addition, the silicon-containing slurry 9 was replaced with a silicon-containing slurry 10, and wet milling was carried out for 3 hours in the same manner as above to obtain a silicon-containing slurry containing silicon particles 10 in which silicon was uniformly dispersed in a dispersion medium. At this time, the diameter of the beads used in the bead mill was 0.1 mm, and the density of the beads was 6.0 g / cm. 3 The bead filling rate was 70%, and the peripheral speed of the bead mill was 12 m / s. The orientation degree F(111) of silicon particles 7 to 9 was all 0.2 or more, and the orientation degree F(111) of silicon particles 10 and 11 was both less than 0.2.
[0153] Examples 4 to 6 Silicon particles 7 to 9, which were measured as the silicon particles according to the <BET specific surface area>, <laser diffraction particle size distribution measurement>, and <specific surface area by laser diffraction particle size distribution meter>, and the ratio of the specific surface area determined by the BET method to the specific surface area calculated by the laser diffraction particle size distribution meter was 2 or more, were used to obtain negative electrode active materials 7 to 9 in the same manner as in Examples 1 to 3. The obtained negative electrode active materials were based on the following <measurement of the orientation degree of silicon particles in the negative electrode active material>, <BET specific surface area of the negative electrode active material powder>, <crystallite diameter of the negative electrode active material powder>, and <measurement of the average particle diameter (D50) of the negative electrode active material powder>, and the orientation degree measurement, BET specific surface area, crystallite diameter, and average particle diameter (D50) of each silicon particle were determined. The results are shown in Table 2.
[0154] Comparative Examples 4 and 5 Silicon particles 10 and 11, which were measured as the silicon particles according to the <BET specific surface area>, <laser diffraction particle size distribution measurement>, and <specific surface area by laser diffraction particle size distribution meter>, and the ratio of the specific surface area determined by the BET method to the specific surface area calculated by the laser diffraction particle size distribution meter was less than 2, were used to obtain negative electrode active materials 10 and 11 in the same manner as in Examples 1 to 3. For the obtained negative electrode active materials, each property was measured in the same manner as in Examples 4 to 6. Using the obtained negative electrode active materials 10 and 11, charge-discharge evaluation was performed in the same manner as in the <evaluation of charge-discharge measurement>. The results are shown in Table 2.
[0155] <Measurement of the orientation degree of silicon particles in the negative electrode active material> The negative electrode active material powder obtained above was filled on the ground glass surface using a glass sample holder for XRD powder measurement, so that the surface height of the sample holder and the surface height of the sample powder were the same. θ-2θ measurement was performed by XRD in the range of 10° to 70°, and the degree of orientation F was calculated from the following formulas (3) and (4). The measurement conditions and the measurement device for XRD were the same as those described above.
number
number
[0156] <BET specific surface area of negative electrode active material powder> The specific surface area of the negative electrode active material powder obtained above was calculated by the BET equation according to the gas adsorption method-constant volume method.
[0157] <Measurement of particle size distribution of negative electrode active material powder> The particle size distribution of the negative electrode active material powder obtained above was measured using distilled water as a measurement solvent and a laser diffraction particle size distribution meter (Mastersizer LMS3000 manufactured by Spectris Inc.) under the same conditions as those for the particle size measurement of the silicon particles. D50 was measured five or more times under the above conditions, and the CV value (standard deviation / average value) of D50 was 5% or less for five consecutive measurements, confirming the stability of the measurement. Then, the specific surface area was calculated from the particle size distribution obtained by the above parameters.
[0158] <Crystallite diameter of negative electrode active material powder> The negative electrode active material powder obtained above was subjected to 2θ-θ measurement by XRD using a SmartLab manufactured by Rigaku Corporation. Using the full width at half maximum (FWHM) of the peak, the crystallite size of the (111) plane was calculated from the following formula (2) by the Scherrer method. The measurement angle was in the range of 10° to 70°. L = Kλ / (βcosθ) (2) In the formula (2), K is a shape factor and is set to 0.9. λ is the wavelength of the X-ray used in the measurement, CuKα=1.5418 Å. β is the peak half-width in radians, θ is the Bragg angle corresponding to the (111) plane, and L is the crystallite diameter.
[0159] The capacity loss rates after 20 cycles of the negative electrode active materials 10 to 14 obtained by the above method were measured by the same method as above. The results are shown in Table 2.
[0160] [Table 2]
[0161] From the measurement of the capacity loss rate after 20 cycles of the half cell, it was found that the smaller the capacity loss rate after 20 cycles, the longer the life of the half cell, indicating excellent cycle properties. As is clear from the results in Tables 1 and 2 above, the secondary battery using the present silicon particles as the negative electrode active material has a small capacity loss rate after 20 cycles, and the resulting secondary battery has excellent cycle properties.
Claims
1. Silicon particles having a ratio of a specific surface area calculated by a laser diffraction particle size distribution analyzer to a specific surface area determined by a BET method of 2 or more.
2. The specific surface area measured by the laser diffraction particle size distribution meter is 35 m 2 The silicon particles according to claim 1, wherein the molecular weight is 1 / g or more. Measurement method: Laser diffraction particle size distribution meter with red laser refractive index of 3.0, absorption rate of 0.2, blue laser refractive index of 2.6, absorption rate of 0.2, powder density of 2.3 g / cm 3 The specific surface area is calculated from the particle size distribution obtained under the above conditions.
3. The specific surface area determined by the BET method is 80 m 2 The silicon particles according to claim 1 or 2, wherein the molecular weight is 1 / g or more.
4. The silicon particles according to claim 1 or 2, having a crystallite diameter calculated by the Scherrer method of 5 nm to 14 nm.
5. A silicon-containing active material containing silicon particles having a ratio of a specific surface area determined by a BET method to a specific surface area calculated by a laser diffraction particle size distribution meter of 2 or more, and a degree of orientation of the (111) plane of the silicon particles, F(111), obtained by the Lotgering method in X-ray diffraction, of 0.03 or more.
6. The silicon particles have a specific surface area of 35 m2 as determined by a laser diffraction particle size distribution meter according to the following measurement method. 2 The silicon-containing active material according to claim 5 , wherein the silicon-containing active material has a molecular weight of 1 / g or more. Measurement method: Laser diffraction particle size distribution meter with red laser refractive index of 3.0, absorption rate of 0.2, blue laser refractive index of 2.6, absorption rate of 0.2, powder density of 2.3 g / cm 3 The specific surface area is calculated from the particle size distribution obtained under the above conditions.
7. The specific surface area determined by the BET method is 50 m 2 The silicon-containing active material according to claim 5 , wherein the molecular weight is 1 / g or less.
8. 6. The silicon particle-containing active material according to claim 5, wherein the volume average particle size is 2 μm or more and 20 μm or less.
9. 6. The silicon particle-containing active material according to claim 5, wherein the crystallite size of silicon in the active material is 40 nm or less.
10. The silicon-containing active material according to claim 5 , which contains a matrix phase containing silicon, oxygen and carbon as main components.
11. A negative electrode active material for a secondary battery, comprising the silicon-containing active material according to claim 5 .
12. A negative electrode comprising the negative electrode active material for a secondary battery according to claim 11.
13. A secondary battery comprising the negative electrode according to claim 12.
Citation Information
Patent Citations
Silicon nanoparticles, active material for negative electrode of non-aqueous secondary battery including the same, and secondary battery
JP2021114483A
Silicon or silicon alloy, composite active material for lithium secondary battery containing the same, and manufacturing method thereof
JP2021180124A